The quinolones - Andriole, Vincent T. (Academic Press, 1988)
The Quinolones covers reviews on the history, chemistry and mechanism of action, in vitro properties, pharmacokinetics, clinical overview, toxicity, adverse effects and drug interactions, and future prospects of the 4-quinolones. The book discusses the microbiology of quinolones, particularly with consideration of the development of resistance, pharmacology, toxicology, and clinical uses. Chemists, microbiologists, pharmacologists and clinicians will find the book useful.